Kontribusi Mahasiswa untuk Mengurangi Tingkat Kemiskinan melalui Entrepreneur School di Desa Wonoharjo, Tanggamus, Lampung - Saepudin saepudin; Marselina Marselina; Heru Wahyudi; Ukhti Ciptawaty (Studi Ekonomi dan Kebijakan Publik, 2023)
Purpose: This community service aims to develop the salak fruit business through the entrepreneur school program by collaborating with students to increase the selling value of the salak fruit so as to reduce the poverty rate. Methodology: The implementation of this community service uses the method of providing motivation and training in developing salak fruit products in farmer groups in Wonoharjo Village, which is carried out directly and data collection through questionnaires. Results: The results of community service show that providing motivation and training for farmer groups in Wonoharjo Village, both those who already have businesses and those who are able to provide business management knowledge and develop salak fruit businesses by utilizing the potential of existing land by working with students, so that salak fruit products can be of high selling value. Conclusion: The synergy framework between salak fruit farmers and academics, consisting of people who have active salak fruit plantations in Dea Wonoharjo, is important because salak fruit farmers will be more optimal in developing their business both offline and online. The program carried out with students has a positive impact as a solution to the problems of salak fruit farmers during the pandemic. Thus, the selling value of salak can be of high selling value. In addition, it is also expected to reduce the level of poverty.